Perceived Risk, Investment Performance and Intentions in Emerging Stock Markets - Trang, Phung Thai Minh; Tho, Nguyen Huu (International Journal of Economics and Financial Issues, 2017)
The study built the new measurement scales of risk perception in investing in stock types trading on the emerging stock market, and then explored the effects of perceived risk on investment performance and intentions of individual investors. The study employed mixed research methods including in-depth interviews, a pilot study involving 50 investors, a survey distributed to 465 retail investors. Results showed that perceived risk had direct positive impact on both investment performance and intentions. Perceived risk also had indirect influence on intentions to invest through investment performance. The study recommended investors drew attention to risk of stocks labelled as “warned”, “controlled”, and “halted trading”. The higher an investor has perceived risk of these stock types, the greater one has been satisfied with one’s decisions on investing, the recent rate of return achieved as well as intended to invest in the next time. Moreover, securities corporations have regularly organized seminars, workshops or training courses about investing in the kinds of stocks and updated regulations of stock investment in time; particularly, improved the quality of listed companies to attract more investors to the stock market. Keywords: Investment performance, Intentions, Perceived risk, emerging stock markets. JEL Classifications: E44, G31